Boredom and lack of control: examination of predictive psychological factors of problematic smartphone use among Hungarian youth (Training and Practice : Journal of Educational Sciences, 2020)
The expansion of smartphone use among young generations is obvious. The related behavioural addiction called problematic smartphone use is a researched phenomenon; several risk and protective factors were identified. Psychological variables - which may predict problematic use - have been examined among teenagers and young adults aged between 14 and 28. According to binary and multiple logistic regression, mainly proneness to boredom and low self-control predicted the phenomenon which can be explained by the need to avoid the relative lack of stimuli and by obsession that controls behavioural addictions.